Transfer at the syntax-pragmatics interface: Pronominal subjects in bilingual Turkish - Haznedar, Belma (Second language research, 2010)
This study investigates the issue of crosslinguistic influence in the domain of subject realization in Turkish in simultaneous acquisition of Turkish and English. The use of subjects in a null subject language like Turkish is a phenomenon linked to the pragmatics-syntax interface of the grammar and, thus, is a domain where crosslinguistic interference is predicted to occur in bilingual acquisition (Hulk and Müller, 2000; Müller and Hulk, 2001). Spontaneous Turkish data collected from one Turkish-English bilingual child, Ali-John, and one Turkish monolingual child, Murat, are compared. Our results reveal that Al¡-John's production of overt subjects in Turkish is more than that of the control child. These findings could be interpreted as due to crosslinguistic influence from English regarding the suppliance of overt subjects in the context of Turkish-English bilingual acquisition.